2018
DOI: 10.3390/ijms19051444
|View full text |Cite
|
Sign up to set email alerts
|

Annexins—Coordinators of Cholesterol Homeostasis in Endocytic Pathways

Abstract: The spatiotemporal regulation of calcium (Ca2+) storage in late endosomes (LE) and lysosomes (Lys) is increasingly recognized to influence a variety of membrane trafficking events, including endocytosis, exocytosis, and autophagy. Alterations in Ca2+ homeostasis within the LE/Lys compartment are implicated in human diseases, ranging from lysosomal storage diseases (LSDs) to neurodegeneration and cancer, and they correlate with changes in the membrane binding behaviour of Ca2+-binding proteins. This also includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 213 publications
(344 reference statements)
0
49
0
1
Order By: Relevance
“…Depletion of AnxA6 could stabilize StARD3/VAP-A and Rab7/protrudin/VAP-A complexes, ensuring re-establishment of MCS between the ER and late endosomes, and eventually the transfer of late endosome-cholesterol to the ER in cells with non-functional NPC1. Although several annexins contribute to endosomal membrane dynamics [62,96,97], only the AnxA1/S100A11 protein complex has yet been associated with MCS formation [90]. While AnxA2 and AnxA6 are also well known to bind S100 proteins, to our knowledge there is no data linking AnxA2 with MCS [90,98].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Depletion of AnxA6 could stabilize StARD3/VAP-A and Rab7/protrudin/VAP-A complexes, ensuring re-establishment of MCS between the ER and late endosomes, and eventually the transfer of late endosome-cholesterol to the ER in cells with non-functional NPC1. Although several annexins contribute to endosomal membrane dynamics [62,96,97], only the AnxA1/S100A11 protein complex has yet been associated with MCS formation [90]. While AnxA2 and AnxA6 are also well known to bind S100 proteins, to our knowledge there is no data linking AnxA2 with MCS [90,98].…”
Section: Discussionmentioning
confidence: 92%
“…We previously demonstrated that AnxA6 overexpression led to late endosome-cholesterol accumulation, a phenotype reminiscent of the NPC1 mutant phenotype [46,62]. This was accompanied by an increased recruitment of AnxA6 to cholesterol-laden late endosomes upon pharmacological NPC1 inhibition, using U18666A, or loading with LDL [43][44][45].…”
Section: Interaction Of Anxa6 With the Rab7-gap Tbc1d15mentioning
confidence: 94%
“…Both ANXA1 and ANXA2 are DEGs in the F8FvsF4F group and they were all highly expressed at four weeks of age in the study. Annexin (ANX) is a kind of protein superfamily with high abundance, calcium-dependent, and binding to negatively charged membrane phospholipids (Rentero et al, 2018;Xie et al, 2018). One of the driving forces underlying cell migration and intercellular interactions is the reorganization of cell membranes and remodeling of the cytoskeleton, processes facilitated by Annexin proteins in multiple systems (Shah, Schiffmacher & Taneyhill, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Both ANXA1 and ANXA2 are DEGs in the F8FvsF4F group and they were all highly expressed at four weeks of age in the study. Annexin (ANX) is a kind of protein superfamily with high abundance, calcium-dependent, and binding to negatively charged membrane phospholipids (Rentero et al, 2018;Xie et al, 2018). One of the driving forces underlying cell migration and intercellular interactions is the reorganization of cell membranes and remodeling of the cytoskeleton, processes facilitated by Annexin proteins in multiple systems (Shah, Schiffmacher & Taneyhill, 2017).…”
Section: Discussionmentioning
confidence: 99%